The Capacitated Sustainable EOQ Models: Models Considering Tax Emissions - Sri Kurnia Dwi Budi Maulana; Dana Marsetiya Utama; Mochammad Samsul Asrofi; Inggit Sekar Ningrum; Nidaul Alba; Hikam Antasyard Ahfa; Thoriq Akbar Zein (Jurnal Teknik Industri, 2020)
The study investigated problems of determining the lot size by considering sustainability and capital constraints for purchasing raw materials and taxes. Using the Sustainable EOQ (SEOQ) models that considered environmental aspects, the researchers also evaluated the capital constraints. The proposed models were used to minimize total inventory costs. In this study, there was a practical numerical analysis and sensitivity analysis to help decision-makers and inventory problems. Finally, the experimental results showed that the proposed models were effectively used to solve the problems.